2018
DOI: 10.1007/s00167-018-5160-7
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of implant integration in partial meniscal replacement: an experimental study on a silk fibroin scaffold in sheep

Abstract: Purpose To restore meniscal function after excessive tissue damage, a silk fibroin implant for partial meniscal replacement was developed and investigated in an earlier sheep model. After 6 months implantation, it showed promising results in terms of chondroprotection and biocompatibility. To improve surgical fixation, the material was subjected to optimisation and a fibre mesh was integrated into the porous matrix. The aim of the study was the evaluation of this second generation of silk fibroin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The most striking outcome of this study was the PG-Pg scaffold's ability to progressively enhance mechanical strength, and reduce cartilage deterioration after 6 months of implantation in rabbit knees. Several clinical studies have demonstrated that meniscal substitutes previously used in clinical practice exhibit varying degrees of decrease in biomechanical properties as tissue infiltration and scaffold degradation occur in vivo [8,16,20,25,27,32]. The PG-Pg scaffold exhibited similar initial mechanical properties to the same material used to replace the rabbit meniscus [32], but their initial mechanics changed as the size of the PG-Pg scaffold changed.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking outcome of this study was the PG-Pg scaffold's ability to progressively enhance mechanical strength, and reduce cartilage deterioration after 6 months of implantation in rabbit knees. Several clinical studies have demonstrated that meniscal substitutes previously used in clinical practice exhibit varying degrees of decrease in biomechanical properties as tissue infiltration and scaffold degradation occur in vivo [8,16,20,25,27,32]. The PG-Pg scaffold exhibited similar initial mechanical properties to the same material used to replace the rabbit meniscus [32], but their initial mechanics changed as the size of the PG-Pg scaffold changed.…”
Section: Discussionmentioning
confidence: 99%
“…From the experimental results, silk fibroin transplantation did not show obvious repair, but still the stent and tissue can not bind tightly and produce inflammation defects. The study of silk fibroin scaffolds still needs to be improved and perfected, but it can not be denied that silk fibroin scaffolds transplantation is still a promising means of meniscus injury repair [18].…”
Section: Silk Fibroin Scaffoldmentioning
confidence: 99%
“…CMI® and Actifit®, are indeed hybrid materials. Collagen Meniscus Implant (CMI®, Ivy Sports Medicine, Germany), commercialized in Europe since 2016, is based on purified bovine collagen I and glycosaminoglycans; whereas Actifit® (Orteq Ltd., UK) contains polycaprolactone and polyurethane [61][62][63] . Moreover, NUsurface® (Active Implants Israel Ltd., Israel), made of polyethylene and polycarbonateurethane, is in the process of FDA approval for total meniscus replacement 61 .…”
Section: Scaffolds Based On Hybrid Materialsmentioning
confidence: 99%